1990
DOI: 10.1080/10862969009547701
|View full text |Cite
|
Sign up to set email alerts
|

Sight Word Reading in Prereaders: Use of Logographic vs. Alphabetic Access Routes

Abstract: In a previous study, Ehri and Wilce (1985) found that prereaders who had not mastered letters were better at forming logographic access routes than letter-sound access routes into memory to read words by sight. Of interest here was whether prereaders who knew all their letters would reveal the same pattern. Preschoolers and kindergartners who could read few if any words out of context but who knew letters were taught to read either six simplified phonetic spellings whose letters corresponded to sounds (e.g., J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 22 publications
2
20
1
Order By: Relevance
“…This shows that the majority possessed the requisite knowledge for phonetic cue reading . Because our target words were spelled phonetically with most of the relevant sounds accessible in the names of the letters, phonetic cue reading should have been easy to employ (Scott & Ehri 1989) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that the majority possessed the requisite knowledge for phonetic cue reading . Because our target words were spelled phonetically with most of the relevant sounds accessible in the names of the letters, phonetic cue reading should have been easy to employ (Scott & Ehri 1989) .…”
Section: Discussionmentioning
confidence: 99%
“…As soon as beginning readers gain even rudimentary knowledge about G-P relations, they become able to learn to read sight words by bonding spellings to pronunciations (Ehri & Wilce 1985;Scott & Ehri 1989;Rack et al 1994). However, because their G-P knowledge and phonemic segmentation skill are limited, their form partial rather than complete connections.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, converging data have established that preschool LNK level is a reliable marker of children's print experience, associated both with other early print-related skills (Adams, 1990;Burgess, 2002;Fritjers, Barron, & Brunello, 2000) and home literacy experiences (Bowey, 1995;Hecht et al, 2000;Lonigan, Burgess, Anthony, & Barker, 1998). Presumably, this unfavorable theoretical and empirical context explains why the in-depth investigation of the role of letter names in literacy development was for many years limited to Ehri's (1983;Ehri & Wilce, 1985;Scott & Ehri, 1990) seminal works.…”
Section: Letter-name Knowledge As a Predictor Of Learning To Readmentioning
confidence: 93%
“…The typical procedure contrasted phonetic spellings, in which some letters matched letter-name sequences included in word pronunciations (e.g., JRF for giraffe), and visual spellings, which were irrelevant regarding word pronunciations, but perceptually highly distinctive (e.g., xGsT for beach) (Ehri & Wilce, 1985). Earlier studies have shown that novice readers (Ehri & Wilce, 1985) and prereaders (Scott & Ehri, 1990), both with a high LNK level, learned the phonetic spellings more easily than the visual ones. This result suggested that children took advantage of the graphophonological information supplied by letters in printed words and letter-name sequences in spoken words.…”
Section: Letter-name Knowledge As a Bridge Towards Alphabetic Literacymentioning
confidence: 97%
“…A great deal of work has been concerned with children's phonemic awareness and its strong relationship to reading and invented spelling ability (Juel, Griffith, & Gough, 1986;Morris, 1993;Scott & Ehri, 1990;Spector, 1995;Yopp, 1992). Richgels, Poremba, and McGee (1996) have described kindergartners' developing phonemic awareness in a naturalistic classroom context as the children engaged in various literacy experiences and activities.…”
mentioning
confidence: 99%